KEBIJAKAN FORMULASI TENTANG TINDAK PIDANA KESUSILAAN DI DUNIA MAYA DALAM PERSPEKTIF HUKUM ISLAM - Laila Mulasari (Faculty of Law, Universitas Diponegoro, 2012)
Related to criminal case based technology, in fact once law inanition (rechtsvacuum) occurred because difficulty in offences formulating (one of them because offences against decency in cyber space) and inability of positive penal law to seek both knowledge and technology development, therefore absence Act Number : 11, 2008 about Information and Electronic Transaction. The interesting problem was related to law enforcement in order to prevent and overcome the offences against decency especially within cyber space through those regulations. Other regulations also related by problem which will researched was Act No. 44, 2008 about Pornography. Historical report showed that, several cases of pornography assessment was failed to be punished because specialist witness within court success convincing judge that contravene morality although proved, it didn't meant pornography. Of course this case contravene with First Moral Principle of Pancasila, “Ketuhanan Yang Maha Esa”, considering that within Islamic law already ruled clearly. Unfortunately, in Indonesia country with majority have Islam religion, precisely Islamic penal law description not known much and learned. Should be, honestly should acknowledge that Islamic penal law also needs studied and found their role in order to Indonesia's penal law renewal. Law enforcement in order to prevent and overcome offences against decency especially within cyber space through positive law have great challenge. One of challenge should create are by transforming Islamic regulation into positive penal law in Indonesia as already occurred within positive Islamic civil law sector. Keywords : Offences Against Decency, Cyberspace, Penal Policy, Islamic Law.